Analysis of consumption trends of antibacterial and antivirus medicines in pharmacies during COVID-19 pandemic in Ukraine - O. M. Zaliska; O. M. Semenov; N. M. Maksymovych; Z. O. Zabolotnya; B. M. Zalisky; I. H. Mudrak (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Rational pharmacotherapy of COVID-19 in the world, treatment protocols, prescriptions of antibacterial (AB), antiviral (AV) medicines have been systematically improved due to updated data of evidence-based medicine. The study aim was to analyze the trends of AB, AV consumption for outpatients with confirmed COVID-19: to study the reasons of the growing demand for AB, AV; optimization of pharmaceutical care directions for rational cost-effectiveness use, prevention antibiotic resistance. Methods - the survey on consumption trends of AB and AV, side effects of AB; survey data of 205 pharmacists, 5 regions of Ukraine; pharmacoeconomic analysis «cost-minimization», content analysis of instructions, side effects. Analysis of surveys showed that the demand on AB, AV increased by 50.1% to 2019, such groups: beta-lactams, respiratory fluoroquinolones, macrolides. We found the most often were released: azithromycin, cefoperazone, cefipime, piperacillin with tazobactam, meropenem. Pharmacists noted that patients often used AB, AV without a prescriptions, it complicates the release from pharmacies. So it is necessary to implement e-prescriptions for AB, AV for monitoring of effectiveness, side effects, to prevent antibiotic resistance in pandemic. We found 53.7% of pharmacists noted about insufficient of trade names, stocks of AB and AV. It is the difficulties to provide outpatients with covid-19. Content-analysis data showed the most common side effects during AB course. We identified the main directions of information pharmacist providing to prevent side effects, antibiotic resistance. We conducted the demand for AV, AV medicines increased by 50.1% vs to 2019. It was identified the AB groups, trade names in high demand. Used pharmacoeconomic analysis «cost-minimization», we established that depending on the manufacturer, an antibiotic course costs differ by 15.1 times. The necessity of including in the list of the reimbursement program «Affordable Medicines» the essential AB, AV, to reduce costs for COVID-19 outpatients was substantiated. We showed 83,1% of pharmacists consider the need of approval, implementation of «Protocol for symptomatic treatment of uncomplicated forms of COVID-19». It will improve the results of pharmaceutical care for COVID-19 patients due to GPP requirements.